Diagnostic Value of Endoscopic and Endoscopic Ultrasound Characteristics of Duodenal Submucosal Tumour-Like Heterotopic Gastric Mucosa - Koichi Eguchi; Kunihiko Aoyagi; Satoshi Nimura; Shotaro Sakisaka (Canadian Journal of Gastroenterology)
OBJECTIVE: Recent studies have reported that duodenal heterotopic gastric mucosa (HGM) has been observed in 8.9% of patients who undergo esophagogastroduodenoscopy. However, there are few reports concerning the endoscopic and endoscopic ultrasound characteristics of submucosal tumour-like HGM in the duodenum.